Affectivity and riskiness of retirement investment decisions. Issue 9 (13th April 2020) - Palmer, Joshua C.; Chung, Yunhyung; Park, Youngkyun; Wang, Gang
Abstract : Purpose: Drawing on broaden-and-build theory and promotion- and prevention-focus theory, the authors examined the role of positive and negative affectivity (PANA) on the riskiness of investment decisions. The authors also examined the mediating impact of financial knowledge network intensity (i.e. the level of communication with financially literate others in employees' social network) on the PANA—riskiness of investment decisions relationship. Design/methodology/approach: Study 1 used a sample of undergraduate students and operationalized risk using a hypothetical investment scenario. Study 2 replicated and extended the Study 1 findings using employees and operationalized risk using their real-world investment allocations. Findings: Both Studies 1 and 2 provided support for the negative direct relationship between NA and the riskiness of investment decisions. Study 2 found PA was marginally positively related to the riskiness of investment decisions. Financial knowledge network intensity mediated the relationship between NA and the riskiness of investment decisions in Study 2. Research limitations/implications: The findings suggest that employees who see the world in a generally negative light tended to have weaker financial knowledge networks, and this may be one mechanism that explains why they make low-risk investments. Practical implications: Financial knowledge networks can provide access to critical information regarding investment opportunities. Socialization training or social mixers can be used to help employees build and improve their financial knowledge networks. Originality/value: The authors integrate the research on PANA, social networks, and investment decisions to illuminate the social network processes that explain how affectivity impacts the riskiness of retirement investment decisions.